Large Deviations for Heavy-Tailed Random Variables in Prospective-Loss Process (Communications in Mathematical Research, 2021)
In this paper, we study the precise large deviations for the prospective-loss process with consistently varying tails. The obtained results improve some related known ones.
Keywords: consistently varying tails; large deviations; prospective-loss process.